PENGARUH BIAYA LINGKUNGAN, KINERJA LINGKUNGAN, DAN SUSTAINABILITY REPORT, TERHADAP KINERJA KEUANGAN (Studi Empiris Perusahaan Manufaktur Terdaftar di BEI 2020 -2023) - Donny Mahendra Pramadya; Ovi Itsnaini Ulynnuha (ITB AAS Indonesia Surakarta, 2025)
The manufacturing industry plays a crucial role in Indonesia’s economic development by creating value-added products and employment opportunities. However, limited adoption of advanced technology and insufficient digital skills among workers hinder the sector’s competitiveness. Additionally, environmental issues, such as industrial pollution, have intensified stakeholder demands for sustainable business practices. This study aims to analyze the influence of environmental costs, environmental performance, and sustainability reporting on the financial performance (ROA) of manufacturing companies listed on the Indonesia Stock Exchange during 2020–2023. A quantitative approach was employed using multiple regression analysis to examine the relationship between these variables. The findings reveal that environmental costs have no significant impact on financial performance. In contrast, environmental performance, as measured by the PROPER rating from the Ministry of Environment and Forestry, shows a positive and significant influence on financial performance. Meanwhile, the economic, environmental, and social dimensions of sustainability reports do not significantly affect financial performance. These results highlight the importance of improving actual environmental performance rather than relying solely on sustainability disclosures to enhance financial outcomes.